P0109EVALUATION AND COMPARISON OF TWO RENAL HISTOLOGICAL CLASSIFICATIONS OF IGA VASCULITIS. (6th June 2020) - EL OUAFI, Zhour; Shourick, Jason; Danthu, Clement; Pillebout, Evangeline; Audemard, Alexandra; Thervet, Eric
Abstract: Background and Aims: Primary IgA nephropathy (IgAN) and IgA vasculitis nephritis (IgAVN) share common features e.g. clinical, histological, pathophysiological. Their prognosis assessment is usually considered to be dependent on histological findings which are therefore useful to establish therapeutic intervention. The validated MEST-C classification is widely used for IgAN. Regarding IgAVN, various classifications are used in clinical practice. However, there is no consensus regarding their feasibility, correlations with renal outcome and their usefulness regarding therapeutic decisions. The aim of this study was to compare the Pillebout and Nochy French classification (PNC), created as a specific IgAVN prognosis scoring system MEST-C classification. Method: Renal biopsies (RB) of patients with IgAVN were selected from two previous national IGAV cohorts and then reclassified according to the MEST-C and PNC classifications. For both classifications, the primary endpoint was the renal remission defined as a final glomerular filtration rate (GFR) greater than 60 ml / min. We also analyse: a) the renal survival defined as the absence of dialysis or transplantation; b) clinical-pathological correlation between the 2 classifications and c) the interobserver reproducibility. Results: 372 RB from 316 patients were analysed, with 240 patients followed for at least 1 year. The median age was 48 yrs (14 to 86), with a sex ratio of 1.76 for men and a median follow-up of 4.3 years (range 1 to 22.7). Renal impairment was more severe over the age of 60 yrs. The presence of general signs, the initial GFR, and hypertension were significantly associated with renal survival. Proteinuria and albuminemia were associated with proliferative lesions (MEST-C score: E, C). The fibrous lesions (MEST-C: T and PNC stage V) were associated with GFR at the end of the follow-up. No significant association was found between the PNC stage and renal survival. Univariate analyses showed significant association with the primary outcome for the MEST-C T variable (p=0.02). However, by multivariate analysis, this association did not persist. The correlation between the observers was better for MEST-C compared with PNC (0.87 vs. 0.75). Conclusion: Our results suggest that MEST-C classification has a good clinical and pathological correlation, a good reproducibility, and is interesting to evaluate the long-term renal outcome of patients with IgAVN. However, the correlation is still not perfect. Indeed, fibrosis was the only pathological feature independently associated with renal endpoints. We suggest that MEST-C is a scoring system which is not fully adapted due to the predominant inflammatory mechanism in IgAVN unlike IgAN. PNC should not be used because of the poor interobserver correlation. It is important to identify new specific IgAVN histological markers, taking into account the inflammatory mechanism, to ensure a more accurate prognostic classification, useful to guide therapeutic strategy.